STUDENTS’ READING STRATEGIES AT ENGLISH EDUCATIONAL DEPARTMENT - Utami Dewi; Maryati Salmiah (STAI Hubbulwathan Duri, 2019)
Reading comprehension is one of the skills that students must have to enrich their knowledge, especially university students. There are two kinds of reading strategies: Top – Down strategy and Bottom – Up Strategy. The aim of this research is to find information about students’ reading comprehension strategies that were applied by the students when they were given reading comprehension text. The research design was qualitative approach. The informants consisted of ten English educational department students, one reading subject lecturer and the head of English educational department. Interview and observation were the major sources of the data to find out the students’ strategies on reading comprehension. Based on those data, it was found that most of the students applied bottom – up strategies in reading comprehension texts